Identification and comprehensive analysis of circRNA–miRNA–mRNA regulatory networks in osteoarthritis - Liu, Xuanzhe; Xiao, Huimin; Peng, Xiaotong; Chai, Yimin; Wang, Shuo; Wen, Gen (Frontiers in Immunology, 2023)
Osteoarthritis (OA) is a common orthopaedic degenerative disease, leading to high disability of daily living. There remains an urgent need to reveal underlying mechanism and identify new therapeutic targets in OA diagnosis and treatment. Circular RNAs (circRNAs) participates in the development of multiple diseases. Many studies have reported regulatory functions of circRNAs to microRNAs (miRNAs) through endogenous competitive mechanism. However, deeper regulatory interplay of circRNAs, miRNAs and target genes in OA remains unclear. Four datasets were downloaded from GEO database and differentially expressed circRNAs (DECs), miRNAs (DEMs) and genes (DEGs) were identified. Functional annotation and pathway enrichment analysis of DEGs and DECs were applied to figure out mainly associated mechanism in OA. Protein-protein network (PPI) was constructed to analyze the function and screen out hub DEGs in OA. Based on the artificial intelligence prediction of protein crystal structures of 2 hub DEGs, TOP2A and PLK1, digitoxin and oxytetracycline was testified to have the strongest affinity, respectively, with molecular docking. Subsequently, overlapping DEMs and miRNAs targeted by DECs obtained target DEMs (DETMs). Intersection of DEGs and genes targeted by DEMs obtained target DEGs (DETGs). Thus, circRNAs-miRNAs-mRNAs regulatory network was constructed by 16 circRNAs, 32 miRNAs and 97 mRNAs. Three hub DECs have the highest number of regulated miRNAs and were verified through in vitro experiments. Additionally, 16 DECs expression level was validated by RT-PCR. In conclusion, we construct circRNAs-miRNAs-mRNAs regulatory network in OA and 3 new hub DECs, hsa_circ_0027914, hsa_circ_0101125 and hsa_circ_0102564 might be identified as novel biomarkers for OA diagnosis.